1989
DOI: 10.1152/ajprenal.1989.257.3.f341
|View full text |Cite
|
Sign up to set email alerts
|

Volume receptors in guinea pig labyrinth: relevance with respect to ADH and Na control

Abstract: We tested the hypothesis that changes in extracellular fluid volume are reflected by pressure changes within structures of the inner ear and that through neural pathways, a control mechanism exerts an influence on antidiuretic hormone (ADH) release and Na excretion. The study was performed on 35 guinea pigs. In protocol 1, 13 animals were studied before and after decompression of the inner ear by bilateral fluid withdrawal in an experimental setting of sustained isotonic expansion that kept the osmoreceptor pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Furthermore, pressure changes of the inner ear have been suggested to control ADH release [17]. The intraluminal stainable homogeneous substance has been shown to contain a large amount of hyaluronic acid [18]; however, protein complexes have also been detected [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pressure changes of the inner ear have been suggested to control ADH release [17]. The intraluminal stainable homogeneous substance has been shown to contain a large amount of hyaluronic acid [18]; however, protein complexes have also been detected [18].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have demonstrated that electrical stimulation of the VIIIth nerve and caloric stimulation of the labyrinth modulate the electrical activity of neurons located in the magnocellular part of the SON and PVN [3] that are responsible for VP release [20]. In addition, pressure changes within the inner ear influence VP plasma levels and Na excretion in acute and anaesthetized guinea-pigs [5] as well as in free-moving animals [33].…”
Section: Discussionmentioning
confidence: 99%
“…the fibroblast-like smooth muscle cells in the spiral ligament and the spiral limbus resemble those of the mesangial cells. Recently it has been postulated that pressure changes may control antidiuretic hormone 76 Yoon/Anniko Alpha-ANP in the Labyrinth (ADH) release via a neural pathway, for instance in the inner ear [12]. In the CNS there occurs ANP-containing neurons which act as a neuromodulator or neurotransmit ter [13].…”
Section: Discussionmentioning
confidence: 99%